2021
DOI: 10.1210/jendso/bvab048.1700
|View full text |Cite
|
Sign up to set email alerts
|

The Application of ThyPRO Questionnaire in Patients With Graves’ Disease Treated With Antithyroid Medications

Abstract: Background: The ThyPRO-39 questionnaire assesses health-related QoL (HRQoL) in patients with benign thyroid disease and has been validated for use in the local setting. The aim of the study is to investigate disease specific health-related quality of life using ThyPRO-39 in patients with newly diagnosed Graves’ disease treated with antithyroid medications over one year. Methods: Patients with newly diagnosed Graves’ disease were recruited in the outpatient setting. The ThyPRO-39 questionnaire was administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous audits of the information recalled by patients on side effects of ATDs indicated that 56 to 70% would take an appropriate action if they have any symptoms suggestive of agranulocytosis. 9,10 In general, information remains sparse in the literature, and no data exists from non-European regions. Equally important is the notion that physicians initiating medication are responsible for preventing, detecting, and managing their complications.…”
Section: Introductionmentioning
confidence: 99%
“…Previous audits of the information recalled by patients on side effects of ATDs indicated that 56 to 70% would take an appropriate action if they have any symptoms suggestive of agranulocytosis. 9,10 In general, information remains sparse in the literature, and no data exists from non-European regions. Equally important is the notion that physicians initiating medication are responsible for preventing, detecting, and managing their complications.…”
Section: Introductionmentioning
confidence: 99%